Surfactant Protein D Level in Cement Workers - Nurlinah Jalil; Sita Laksmi Andarini; Muhammad Ilyas; Feni Fitriani Taufik (Jurnal Respirologi Indonesia, 2022)
Background: Pneumoconiosis occurs almost all over the world. Pneumoconiosis is a threat to cement workers. Serological abnormalities are observed in pneumoconiosis. Surfactant protein D (SP-D) levels were increased in workers exposed to silica. SP-D may be useful as a biomarker for the early diagnosis of pneumoconiosis but it has not been studied in Indonesia.Methods: This cross-sectional study was conducted with consecutive sampling technique. The number of subjects was 61 people, consisting of 44 workers exposed to cement and 17 controls from September 2017 to March 2018. Serum level of SP-D was measured using ELISA method. Cement exposed workers were workers in the production area and workers in quarry areas.Results: All of the study subjects were male (100%) with mean age of 42.5 years old. The youngest and oldest subjects were 21 and 55 years old, respectively. Majority of the subjects was in the normal weight group (47.7%). Based on smoking history, there were 26 subjects (59.1%) had never smoked, 12 subjects (27.3%) as smokers, and 6 subjects (13.6%) as former smokers. Duration of exposure <10 years was found in 9 subjects (20.5%) while exposure ≥10 years was observed in 35 subjects (79.5%). Good category of using self-respiratory safety instrument was observed in 5 subjects (11.4%), moderate category in 36 subjects (81.8%) and poor category in 3 subjects (6.8%). Mean serum SP-D levels in the exposed group was 111.027 ng/ml and in control group was 67.648 ng/ml. Serum SP-D levels were significantly higher in the exposed group than control group (P=0.014).Conclusion: Serum SP-D levels was statistically higher in the exposed group than in control group.